(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Bioengineered scaffolds with optimized osteoconductive and osteoinductive properties are highly desirable in bone tissue regeneration. Stochastic porous structures, resembling human trabecular bones, have gained increasing attention due to their suitability and superior performance in bone healing compared to regular porous architectures. In this study, we designed six trabecular-like porous scaffolds with varying porosity and surface area-to-volume (S/V) ratios. The scaffolds were fabricated using pure Titanium via selective laser melting (SLM), and their morphological characteristics were analyzed via micro computed tomography (µCT). Quasi-static compression testing was conducted to assess mechanical properties. The results showed that the as-built scaffolds exhibited a porosity range 67–71%, an average pore diameter ranging 440–565 µm, a quasi-elastic gradient between 2.6–3.5 GPa, and a yield strength of 44–58 MPa. These values closely match those of the cortical bone, indicating potential for orthopedic applications by mitigating stress shielding and enhancing implant longevity. Additionally, the permeability and wall shear stress (WSS) were measured to predict cell growth performance in the scaffolds. The as-built models have a satisfactory permeability range of 6x10-9 to 15x10-9 m2, which is higher than that of cancellous bone, benefitting prospects for nutrient flow and by-product removal that encourage osteoblastic mineralization.